Global and East Asia tracheal, bronchus, and lung cancer trend analysis from 1990 to 2021 and forecast trend from 2021 to 2035 - Ding, Jian; Guo, Weizhen; Xue, Qian; Cheng, Gang; Zhang, Lu; Wu, Di; Gao, Yating; Yang, Cheng; Tong, Jiabing; Li, Zegeng (Frontiers in Oncology, 2025)
Background and AimsThis study aimed to evaluate the trends in incidence, mortality, and disability-adjusted life years (DALYs) for trachea, bronchus, and lung (TBL) cancer globally and in East Asia from 1990 to 2021.MethodsWe analyzed TBL cancer data from the Global Burden of Disease (GBD) 2021 study, focusing on five East Asian countries. Socioeconomic contexts were examined using sociodemographic indices. Trends in disease metrics were analyzed using time-segmented link-point regression to determine the average annual percentage change (AAPC). A Bayesian Age-Period-Cohort (BAPC) model was applied to forecast the future disease burden from 2022 to 2030.ResultsGlobally and in East Asia, significant increases were observed in the incidence, mortality, and DALYs related to TBL cancer from 1990 to 2021. China had the highest rates of incidence (934,704; 95% UI, 750,040 to 1,136,938), mortality (814,364; 95% UI, 652,636 to 987,795), and DALYs (18,920,203; 95% UI, 15,100,681 to 23,111,519), while Mongolia had the lowest. Ambient particulate matter pollution was identified as the main risk factor for TBL cancer mortality both globally and in most East Asian countries. Notably, global TBL cancer incidence spikes occurred during 1999-2012 and 2019-2021 (AAPC: 1.170 [95%, 1.115 to 1.225] and 1.658 [95%, 0.604 to 2.723], respectively). In Mongolia, TBL cancer incidence showed variable trends. The increases in global and East Asian DALY rates were attributed to population aging and growth, while epidemiological shifts have contributed to reduced rates. Except for Democratic People’s Republic of Korea, DALY risk trends were generally declining across the other East Asian countries.ConclusionThere has been a significant increase in the incidence and mortality rates of TBL cancer both globally and in East Asia from 1990 to 2021, with environmental particulate matter pollution potentially serving as a strongly correlated risk factor. There is an urgent need to enhance prevention, early detection, and treatment measures, particularly in high-risk regions.